2011
DOI: 10.3341/kjo.2011.25.4.252
|View full text |Cite
|
Sign up to set email alerts
|

Laser Peripheral Iridotomy with Iridoplasty in Primary Angle Closure Suspect: Anterior Chamber Analysis by Pentacam

Abstract: PurposeTo compare conventional laser peripheral iridotomy (LPI) and LPI combined with laser peripheral iridoplasty in eyes with primary angle closure suspect (PACS) by assessment of anterior chamber dimensional changes using a Pentacam.MethodsForty-eight eyes of 24 subjects with bilateral PACS were recruited consecutively. Each eye was randomly allocated to treatment with conventional LPI, argon LPI only, or LPI plus iridoplasty, which consisted of simultaneous argon LPI and peripheral iridoplasty. Anterior ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…In a study conducted by Lee et al, 25 the authors compared conventional LPI alone and LPI combined with LPIp in eyes diagnosed as PACS by the assessment of anterior-chamber dimensional changes using a Pentacam. In this study, conventional LPI was performed on 1 randomly selected eye by a single glaucoma specialist using an argon laser, and a week later, the complementary eye was treated with LPI combined with LPIp.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Lee et al, 25 the authors compared conventional LPI alone and LPI combined with LPIp in eyes diagnosed as PACS by the assessment of anterior-chamber dimensional changes using a Pentacam. In this study, conventional LPI was performed on 1 randomly selected eye by a single glaucoma specialist using an argon laser, and a week later, the complementary eye was treated with LPI combined with LPIp.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that included PACS for the comparison of LI and LI combined with PI assessed by Pentacam, postprocedure IOP did not significantly differ between the two groups during 3 months after treatment when the baseline IOP values did not significantly differ either between eye treated by conventional LI and LI plus iridoplasty (Lee et al. ). In a randomized pilot study that included synechial PAC or PACG, IOP was reduced significantly after LI or LI plus PI.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al. () have reported that LI plus PI can improve the mid‐to‐peripheral ACD increase assessed by Pentacam in subjects with PACS compared to conventional LI. Previous studies including a population study have also revealed that 19.4% to 42.9% of the anterior chamber angles of angle closure eyes after undergoing LI have remained closed (Alsagoff et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Lee et al. ). The current consensus view is that APLI alone is of limited use outside of the acute setting, where it may be used to break the attacks of acute angle closure (Ng et al.…”
Section: Treatmentmentioning
confidence: 98%
“…, ; Lee et al. ). In one study, 87% of plateau iris eyes treated with ALPI had open angles at the end of long‐term follow‐up (mean 79 months) after a single treatment, with no need for future filtration surgery (Ritch et al.…”
Section: Treatmentmentioning
confidence: 99%